The Interconnection between Quranic Maqasid and the Interpretation of Mawdu’i - Bakar, Sahlawati Abu; Hussin , Haziyah; Abdullah, Wan Nasyruddin Wan (International Journal of Psychosocial Rehabilitation, 2020)
Many Quranic scholars talk about the Quranic maqasid as well as the concept of mawdu’i interpretation or thematic. However, most studies discuss this as two separate aspects. This article aims to describe the relationship between the Quranic maqasid and the interpretation of mawdu’i. This study uses the text analysis method and the results of the study found that in principle the Quranic maqasid is related to the concept of mawdu’i in terms of the unity of the themes found in the Quran. The Quranic Maqasid is the main purpose of the Quran that the interpreter should accomplish in his interpretation. Whereas the interpretation of the mawdu’i is an approach to interpret the verses of the Quran that are grouped together in one theme and relate it to the Quranic maqasid. In addition, the interpretation of the mawdu’i also examines issues in the Quran based on the Quranic maqasid. The study found that there are three links between the Quranic maqasid and the interpretation of the mawdu’i, firstly the aspect of the principle of interpretation, secondly the elements in Quranic maqasid and the interpretation of the mawdu’i and thirdly the interpretation of al-maqasidi. Thus, the Quranic maqasid can be realized by examining its relationship to the interpretation of the mawdu’i and its approach to the interpretation of the Quran.